61 Bringing simulation and skills into the neonatal academic module - Leonard, Elizabeth; Ross, Ali (Archives of disease in childhood, 2023)
The Neonate in the Ward Environment was developed three years ago to address the gaps in neonatal care highlighted in a Quality Improvement programme. GOSH is very good at looking after the multiple specialities within the hospital and neonates have excellent specialist care. What was lacking was the theory behind normal neonatal care and understanding the importance of that care (WHO 2017). For the latest cohort, a skills and simulation day was added to the timetable for the first time (Morfoot and Stanley, 2018).The aim of the day was to enable the students to practice clinical skills in the morning, use those skills and academic thinking and reflection in the simulation and to encourage self-efficacy and team work (Crocetti 2014). It was necessary to ensure that basic elements were included in the skills and that scenario were relevant to the teaching and would also require the students to understand the rationale and evidence behind their actions. The skills were taught by senior experienced neonatal nurses to ensure correct evidenced based care. Scenario were checked by subject matter experts and coordinated by the experienced simulation team.From a teaching point of view the day involved considerable preparation and was resource intensive. For the students, many who had not been in a face to face teaching since the pandemic, the experience of being together was excellent but the face to face simulation made anxiety a problem (Hayden et al 2014). However, after the first simulation scenario, the debrief afterwards was more relaxed enabling the candidates to reflect on their part and to show they understood the physiology and nursing care behind the scenario (Cooper 2014).As this was the first time it had run it was pleasing to get positive evaluation for the session to be incorporated into future cohorts.